Penerapan Numbered Heads Together Untuk MeningkatkanMotivasi Dan Komunikasi Belajar Matematika Pada SiswaKelas VII Semester Gasal SMP Negeri 3 Sragen Tahun2015/2016 - Hermawati, Rahmi (2016)
Rahmi Hermawati/ A 410 120 059. The Implementation Of Numbered Heads Togethe rto Increase Motivation and communication in Learning Mathematics. Research of paper. Faculty of Teaching and Education Training. Muhammadiyah University of Surakarta, 2016. This research aimed at increasing motivation and communication in learning mathematics of seventh grade students of SMP Negeri 3 Sragen in the mathematics learning using Numbered Heads Together. Type of research used was a qualitative research using Classroom Action Research. Subjects of this research were teachers and students of SMP Negeri 3 Sragen. The students who became the subjects of action receiving were the seventh grade students of A. The students were as many as 32 students, consisting of 16 male students and 16 female students. The technique of data collection used including observation, field records, and documentation. The technique of data analysis in this research was data collection, data reduction, data display and conclusion. To ensure the validity of in this research, the researcher conducted triangulation. The result of the research showed the indication of increase in motivation and communication in learning mathematics which was viewed from the indicators of: being diligent in doing the tasks from 21.875% into 75%, being resilient in facing difficulty from 18.75% into 71.875%, showing interest in many kinds of problems from 18.75% into 71.875%, conveying the ideas of mathematics through conversation or oral from 15.625% into 71.875%, describing ideas into the mathematics model from 15.625% into 68.75%, writing ideas in the form of visual from 12.5% into 65.625%, and explaining the concept of mathematics from 9.375% into 65.625%.